Estimated Prevalence of Hypertension and Undiagnosed Hypertension in a Large Inpatient Population: A Cross-sectional Observational Study. (22nd May 2021) - Mahdi, Adam; Armitage, Laura C; Tarassenko, Lionel; Watkinson, Peter
Abstract: Background: Hypertension is a major cause of morbidity and mortality. In community populations the prevalence of hypertension, both in diagnosed and undiagnosed states, has been widely reported. However, estimates for the prevalence of hospitalized patients with average blood pressures (BPs) that meet criteria for the diagnosis of hypertension are lacking. We aimed to estimate the prevalence of patients in a UK hospital setting, whose average BPs meet current international guidelines for hypertension diagnosis. Methods: We performed a retrospective cross-sectional observational study of patients admitted to adult wards in 4 acute hospitals in Oxford, United Kingdom, between March 2014 and April 2018. Results: We identified 41, 455 eligible admitted patients with a total of 1.7 million BP measurements recorded during their hospital admissions. According to European ESC/ESH diagnostic criteria for hypertension, 21.4% (respectively 47% according to American ACC/AHA diagnostic criteria) of patients had a mean BP exceeding the diagnostic threshold for either Stage 1, 2, or 3 hypertension. Similarly, 5% had a mean BP exceeding the ESC/ESH (respectively 13% had a mean BP exceeding the ACC/AHA) diagnostic criteria for hypertension, but no preexisting diagnostic code for hypertension or a prescribed antihypertensive medication during their hospital stay. Conclusions: Large numbers of hospital inpatients have mean in-hospital BPs exceeding diagnostic thresholds for hypertension, with no evidence of diagnosis or treatment in the electronic record. Whether opportunistic screening for in-hospital high BP is a useful way of detecting people with undiagnosed hypertension needs evaluation.